Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/os.13472
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Joint after Opening Wedge High Tibial Osteotomy: A Comparative Study of Uniplane versus Biplane Osteotomies

Abstract: Objective To the best of our knowledge, there has been no comparative study of changes in radiographic parameters in the sagittal plane between biplane opening wedge high tibial osteotomy (OWHTO) with plate fixation and uniplane OWHTO with spacer implantation. The aim of the study was to compare sagittal radiographs between the procedures of biplane and uniplane OWHTOs in patients with genu varum and to investigate the impact on the patellofemoral joint. Methods A retrospective study of 71 patients (58.0 ± 5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In the present study, the AP displacement of the osteotomized fragment was defined The values are given as mean ± standard deviation.AP: anteriorposterior, TT: tibial tuberosity, FTA: femoral tibial angle, PTS: posterior tibial slope, mBPI: modified Blackburne-Peel index, mCDI: modified Caton-Deschamps index. biplane ascending osteotomy showed more rearward movement of the TT from the proximal fragment than the uniplane osteotomy [23]. Although they reported good reproducibility of the measuring method, it may be potentially affected by the change in PTS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, the AP displacement of the osteotomized fragment was defined The values are given as mean ± standard deviation.AP: anteriorposterior, TT: tibial tuberosity, FTA: femoral tibial angle, PTS: posterior tibial slope, mBPI: modified Blackburne-Peel index, mCDI: modified Caton-Deschamps index. biplane ascending osteotomy showed more rearward movement of the TT from the proximal fragment than the uniplane osteotomy [23]. Although they reported good reproducibility of the measuring method, it may be potentially affected by the change in PTS.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to these changes in the sagittal plane, a few studies showed a change of the osteotomized fragment in the AP direction after HTO, i.e. in OWHTO, the TT is not only moved to the distal direction but also moved to the posterior direction in relation to the biplane osteotomy [23]. No comparative study has been conducted to assess changes in the AP direction of the distal fragment in relation to the proximal fragment between OWHTO and CWHTO, and the present study focused on it.…”
Section: Discussionmentioning
confidence: 99%